PENGARUH SYSTEMIC FAIRNESS DARI LAYANAN INTERNET BANKING TERHADAP CUSTOMER SATISFACTION DENGAN CUSTOMER TRUST DAN CUSTOMER PERCEIVED VALUE SEBAGAI VARIABEL INTERVENING - Reza Putra Pratama (Jurnal Manajemen dan Pemasaran Jasa, 2014)
The background of this research is to investigate and analyze the effect of systematic fairness from internet banking services to customer satisfaction with customer trust and customer perceived value as intervening variable. The objective of this research findings in internet banking, fairness that includes distributive fairness, procedural fairness and informational fairness is positivelyrelated to customer satisfaction. Trust is identified as the key mediator of fairness to customer satisfaction. The design of this research model based on equity theory and relationship marketing theory that incorporates fairness, trust, perceived value and customer satisfaction. The participants of this sample includes 100 respondents which are the customer of bank on Jakarta. Data analysis applied measuring method on Structural Equation Method (SEM) by using the statistic Lisrel. The result of research indicated that,, systematic fairness has a positive impact to customer satisfaction as well as trust and perceived value of the customer to the satisfaction.Keywords: systematic Fairness, Customer Satisfaction, Trust, Perceived Value.